WAYS OF OPTIMIZATION OF THE MILITARY PHARMACEUTICAL STORAGE SYSTEM WORK - N. I. Khomutetskaya (Farmaciâ i Farmakologiâ (Pâtigorsk), 2015)
The article is devoted to the optimization of the system of military-pharmaceutical storage logistics. The features of the work of military medical stores, the main tasks of which is not only to make a profit, but a willingness to provide military hospitals, military pharmacies, and with military units medical supplies for line work as well as in terms of emergency, and armed conflicts. In the studies we covered groups of operations which were conducted in the storage, and using the methods of comparative analysis and functional modeling we have determined “weak spots”, where there is possible to reduce the losses and optimize the work of a storage area. Article describes the ways and directions of the military medical storages, which will allow the increase of their work efficiency and to reduce the losses in their activity process.